Opposite Nuclear Dynamics of Two FRH-Dominated Frequency Proteins Orchestrate Non-Rhythmic Conidiation in Beauveria bassiana - Sen-Miao Tong; Ding-Yi Wang; Qing Cai; Sheng-Hua Ying; Ming-Guang Feng (Cells, 2020)
Non-rhythmic conidiation favors large-scale production of conidia serving as active ingredients of fungal insecticides, but its regulatory mechanism is unknown. Here, we report that two FREQUENCY (FRQ) proteins (Frq1/2) governed by a unique FRQ-interacting RNA helicase (FRH) orchestrate this valuable trait in Beauveria bassiana, an asexual insect-pathogenic fungus. Frq1 (964 aa) and Frq2 (583 aa) exhibited opposite expression dynamics (rhythms) in nucleus and steadily high expression levels in cytoplasm under light or in darkness no matter whether one of them was present or absent. Such opposite nuclear dynamics presented a total FRQ (pooled Frq1/2) level sufficient to persistently activate central developmental pathway in daytime and nighttime and supports continuous (non-rhythmic) conidiation for rapid maximization of conidial production in a fashion independent of photoperiod change. Importantly, both nuclear dynamics and cytoplasmic stability of Frq1 and Frq2 were abolished in the absence of the FRH-coding gene nonessential for the fungal viability, highlighting an indispensability of FRH for the behaviors of Frq1 and Frq2 in both nucleus and cytoplasm. These findings uncover a novel circadian system more complicated than the well-known Neurospora model that controls rhythmic conidiation, and provide a novel insight into molecular control of non-rhythmic conidiation in B. bassiana.